Experimental and Simulation Results for the Impact of a Rotating Flexible Link with a Granular Material. (13th March 2014) - Marghitu, Dan; Lee, Seunghun; Marghitu, Daniela
In this paper, a rotating flexible link impacting a granular media is studied. The influences of initial impact velocity and impact angle are examined. The resistance forces are expressed as the sum of a dynamic frictional force (velocity-dependent) and a static resistance force (depth dependent). The penetrating angle increases with initial impact velocity as expected. However, the stopping time decreases with initial impact velocity for all initial impact angles for the considered system.